2009
DOI: 10.1111/j.1939-165x.2009.00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute phase proteins in the diagnosis of bovine subclinical mastitis

Abstract: The results suggest that measuring haptoglobin and amyloid A in milk is more accurate than serum analysis for the diagnosis of subclinical mastitis in Holstein cows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 19 publications
8
45
0
2
Order By: Relevance
“…In studies of bovine respiratory disease, peak levels of serum SAA and HPT were reported during week 3 of an outbreak of respiratory disease in calves caused by respiratory syncytial virus (Orro et al, 2011), while experimental infection with respiratory syncytial virus caused maximal increases in serum levels of HPT and SAA in cattle as early as 7-8 days following inoculation (Heegaard et al 2000). Of the bovine diseases studied, however, APP expression has been investigated most extensively during mastitis in lactating dairy animals (Safi et al, 2009;Suojala et al, 2008;Eckersall et al, 2006Eckersall et al, , 2001Grönlund et al, 2003;Hirvonen et al, 1999). Mastitis is defined as an inflammation of the mammary gland, and is considered the most dominant and costly of diseases to affect lactating dairy cattle.…”
Section: Modulation Of Acute Phase Proteins During Ruminant Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In studies of bovine respiratory disease, peak levels of serum SAA and HPT were reported during week 3 of an outbreak of respiratory disease in calves caused by respiratory syncytial virus (Orro et al, 2011), while experimental infection with respiratory syncytial virus caused maximal increases in serum levels of HPT and SAA in cattle as early as 7-8 days following inoculation (Heegaard et al 2000). Of the bovine diseases studied, however, APP expression has been investigated most extensively during mastitis in lactating dairy animals (Safi et al, 2009;Suojala et al, 2008;Eckersall et al, 2006Eckersall et al, , 2001Grönlund et al, 2003;Hirvonen et al, 1999). Mastitis is defined as an inflammation of the mammary gland, and is considered the most dominant and costly of diseases to affect lactating dairy cattle.…”
Section: Modulation Of Acute Phase Proteins During Ruminant Diseasementioning
confidence: 99%
“…Veterinary Biomarker Discovery: Proteomic Analysis of Acute Phase Proteins 191 2.1 Modulation of acute phase proteins during disease in swine Alteration in APP expression has been associated with a number of food animal diseases (Table 1), including mastitis, metritis, and amyloidosis in lactating dairy cattle (Chan et al, 2010;Safi et al, 2009;Suojala et al, 2008;Eckersall et al, 2001Eckersall et al, , 2006Takahashi et al, 2006;Grönlund et al, 2003Grönlund et al, , 2005; sepsis, trauma, and respiratory diseases in swine (Amory et al, 2007;Sorensen et al, 2006;Hultén et al, 2003;Heegaard et al, 1998;Eckersall et al, 1996); infectious bronchitis virus in chickens (Nazifi et al, 2011); respiratory diseases in beef cattle (Orro et al, 2011;Heegaard et al, 2000;Godson et al, 1996;Horadagoda et al, 1995); as well as pulmonary damage and caseous lymphadenitis in sheep (Eckersall et al, 2007;Pfeffer and Rogers, 1989 In swine, increased levels of serum HPT have been associated with pathological indications of Mycoplasma hyopneumoniae, a leading cause of porcine enzootic pneumonia (Amory et al, 2007). Similarly, serum concentrations of HPT and SAA were elevated in pigs with experimentally induced Actinobacillus pleuropneumoniae pneumonia Heegaard et al, 1998).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…APPs are alternative biomarkers of mastitis and may increase before macroscopic changes in the milk. However, in subclinical mastitis milk is much better than blood plasma for APP estimation (Safi et al 2009). It is also known that changes in the oxidation state of organism, cell metabolism and stress may have strong influence on blood APPs value.…”
Section: Introductionmentioning
confidence: 99%
“…In Swiss veterinary practice, the diagnosis of subclinical mastitis is based on the results of a California Mastitis Test, SCC, or bacteriological culture (BC). However, it has been postulated that the California Mastitis Test and SCC are not sensitive enough to identify subclinical infection, and do not qualify as reliable screening tests (Middleton et al, 2004;Safi et al, 2009). As well, SCC usually remains elevated for several weeks after successful treatment (Pyörälä, 1988) and is affected by many physiological factors, such as age, lactation period, parity, stress, season, and intra-or extramammary infection (Jensen and Eberhart, 1981;Bielfeldt et al, 2004;Sharma et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Serum amyloid A migrates passively through the blood-milk-barrier because of the increased permeability of inflamed mammary tissue (Eckersall et al, 2001;Kovac et al, 2011), and it is also locally produced as a particular isoform (M-SAA3) by a restricted population of bovine mammary epithelial cells Gerardi et al, 2009;Molenaar et al, 2009). Serum amyloid A and M-SAA3 together are called milk amyloid A (MAA), which is measurable in milk samples using a commercially available ELISA (Tridelta Development Ltd., Maynooth, Ireland), and MAA has proven to be a reliable biomarker for both subclinical mastitis (Eckersall et al, 2006;Gerardi et al, 2009;Safi et al, 2009;Pyörälä et al, 2011) and clinical mastitis (Molenaar et al, 2009;Kovac et al, 2011;Pyörälä et al, 2011).…”
Section: Introductionmentioning
confidence: 99%